EFEKTIVITAS PROGRAM CORPORATE SOCIAL RESPONSIBILITY (CSR) PT. PERTAMINA DI TAMBAKREJO, KECAMATAN SEMARANG UTARA, KOTA SEMARANG - Ristiawan, Muhammad Ibnu; Lestari, Hesti (Journal of Public Policy and Management Review, 2019)
Corporate Social Responsibility is an obligation carried out by the company and regulated in article 74 paragraphs (1) of Law Number 40 of 2007 concerning Limited Liability Companies, but in its implementation, the program is not perceived in creating community independence. The purpose of this study is to determine the effectiveness of PT Pertamina's CSR program carried out in Tambakrejo, North Semarang, Semarang City. This research is qualitative descriptive research. This research uses the theory of effectiveness from Sutrisno. The results show that there are five areas of Pertamina's CSR program in Tambakrejo, namely CSR in the fields of environment, education, economics, infrastructure, and health. The effectiveness of PT Pertamina's CSR program in Tambakrejo can be concluded that the result is not optimal yet since Tambakrejo people do not fully understand every Pertamina's CSR program, the target of CSR programs that have not touched all communities, and lack of timeliness in the implementation of activities. Some programs such as economic CSR programs and health CSR programs, have not been able to achieve the goals set by the company and have less impact on beneficiaries. The determining factors in this program are company resources, namely the lack of CDO officers, community conditions that affect the acceptance of CSR programs, and budget constraints so that Pertamina has limitations in choosing targets and programs. The environmental conditions that hinder the implementation and development of programs and the individual’s capacity that has the motivation to develop, the training and mentoring carried out by various stakeholders, and the group capacity built by individual capacity, leadership, and support